2019
DOI: 10.1155/2019/2973190
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Vehicle Ride Comfort Optimization Based on Intelligent Algorithms and Nonlinear Damping

Abstract: The method chosen to conduct vehicle dynamic modeling has a significant impact on the evaluation and optimization of ride comfort. This paper summarizes the current modeling methods of ride comfort and their limitations. Then, models based on nonlinear damping and equivalent damping and the multibody dynamic model are developed and simulated in Matlab/Simulink and Adams/Car. The driver seat responses from these models are compared, showing that the accuracy of the ride comfort model based on nonlinear damping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The schematic construction of the developed PZ damper is shown in Figure 1a. In the hydraulic cylinder (1) there is hydraulic oil, which is forced through between the chambers of the cylinder by a moving piston (2). The results obtained from experimental and numerical studies confirmed the possibility to use controlled dampers with a piezoelectric valve to damp vibrations of vehicles and machines.…”
Section: Construction Of a Piezoelectric Valve (Pz) Dampermentioning
confidence: 69%
See 2 more Smart Citations
“…The schematic construction of the developed PZ damper is shown in Figure 1a. In the hydraulic cylinder (1) there is hydraulic oil, which is forced through between the chambers of the cylinder by a moving piston (2). The results obtained from experimental and numerical studies confirmed the possibility to use controlled dampers with a piezoelectric valve to damp vibrations of vehicles and machines.…”
Section: Construction Of a Piezoelectric Valve (Pz) Dampermentioning
confidence: 69%
“…The schematic construction of the developed PZ damper is shown in Figure 1a. In the hydraulic cylinder (1) there is hydraulic oil, which is forced through between the chambers of the cylinder by a moving piston (2). Chambers of the hydraulic cylinder are tightly separated (seal on the piston), and the fluid flows through a duct (3), and next through the gap in the piezoelectric valve (4).…”
Section: Construction Of a Piezoelectric Valve (Pz) Dampermentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, different methods were developed where the control signal is determined on the basis of the measurement signals. In multi-body systems, Zero Residual Vibration-Derivative methods [22,23] are used to determine the control signal. Another solution to the problem is to use Hybrid Prediction Control [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…10 He et al proposed a ride comfort optimization method based on nonlinear damping of suspension and intelligent algorithms, which could decrease the root mean square (RMS) of dynamic tire load of front and rear wheels and thus improve the ride comfort of passenger cars. 11 Gedik et al investigated the effect of parabolic speed hump profiles on ride comfort and driving safety under variable vehicle speeds, which proved that vehicle speed and parabolic speed hump height were the most important parameters that affect ride comfort and driving safety. 12 The above research studies can provide a good reference for this article, but there are few research studies on the complex and harsh “off-road”, on which the construction vehicles often walk.…”
Section: Introductionmentioning
confidence: 99%